A methodological approach for assessing the uptake of core outcome sets using ClinicalTrials.gov: findings from a review of randomised controlled trials of rheumatoid arthritis. (17th May 2017) - Kirkham, Jamie J; Clarke, Mike; Williamson, Paula R
Abstract : Objective  To assess the uptake of the rheumatoid arthritis core outcome set using a new assessment method of calculating uptake from data in clinical trial registry entries. Design  Review of randomised trials. Setting  ClinicalTrials.gov. Subjects  273 randomised trials of drug interventions for the treatment of rheumatoid arthritis and registered in ClinicalTrials.gov between 2002 and 2016. Full publications were identified for completed studies from information in the trial registry or from an internet search using Google and the citation database Web of Science. Main outcome measure  The percentage of trials reporting or planning to measure the rheumatoid arthritis core outcome set calculated from the information presented in the trial registry and compared with the percentage reporting the rheumatoid arthritis core outcome set in the resulting trial publications. Results  The full rheumatoid arthritis core outcome set was reported in 81% (116/143) of trials identified on the registry as completed (or terminated) for which results were found in either the published literature or the registry. For trials identified on the registry as completed (or terminated), using information only available in the registry gives an estimate for uptake of 77% (145/189). Conclusions  The uptake of the rheumatoid arthritis core outcome set in clinical trials has continued to increase over time. Using the information on outcomes listed for completed or terminated studies in a trial registry provides a reasonable estimate of the uptake of a core outcome set and is a more efficient and up-to-date approach than examining the outcomes in published trial reports. The method proposed may provide an efficient approach for an up-to-date assessment of the uptake of the 300 core outcome sets already published.